Measurement of Product Costing for Business Process at SMK YPPS Sumedang: Perhitungan Harga Pokok untuk Bisnis Usaha di SMK YPPS Sumedang - Hapsari*, Dini Wahjoe; Salim, Dwi Fitrizal; Pratomo, Dudi; Ellyana, Kharisma; Zikro, Alvin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
SMK YPPS Sumedang is a formal education unit that organizes vocational education focusing on hospitality, culinary, and fashion expertise. The school has provideda practice room to support students' business expertise. Business management must be equipped with financial management skills. Service and manufacturing industries require the accurate calculation of the produc costingto determine selling prices. The obstacle faced by the school is that students have not been able to calculate the cost of goods and selling price accurately Students need additional insight related to these calculations. The team of community service activities was implemented in class X, consisting of students of the hospitality, catering, and fashion programs. This activity used a combination of investigative, quantitative and descriptive approach.In addition to providing material, students work on pre-test and post-test questions. The test scores showed an increase after students obtained the material. The results of the questionnaire filled out by students showed 94% agreed that the implementation of the activity went according to the objectives, 97% agreed that the activity program suited the needs of the partners (students of SMK YPPS), 90% agreed that the implementation of the program was relatively sufficient, 96% agreed that the implementation team was friendly and helpful, 97% agreed that this program was sustainable